2008
DOI: 10.1177/1559827608323214
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Health Promotion by Chiropractors

Abstract: Other areas where chiropractors could potentially help their patients to pursue healthier choices-most notably smoking cessation-are addressed far less frequently. Abstract: Chiropractic care includes a variety of minimally invasive approaches, with both treatment and prevention as essential elements of clinical practice. Although chiropractic adjustment (manipulation) is the signature therapy and best-known identifier of the profession, the practice of chiropractic involves more than manual therapeutics. In g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The investigators then evaluated the frequency, after the revamped public health curriculum was implemented, with which interns (with clinician approval) actually delivered evidence-based preventive care advice to their patients when factors indicating such a need were present. 9,10 The audit postcurriculum change of Globe et al 9 showed virtually no difference in intern (and clinician) behaviors. Of 408 charts examined (204 before and 204 after the curriculum change), there were only 4 documented instances of appropriate recommendations for any of the 9 preventive health service categories, a startlingly low success rate of 1%.…”
Section: Upgrading the Clinical Preventive Services Curriculum-model mentioning
confidence: 98%
“…The investigators then evaluated the frequency, after the revamped public health curriculum was implemented, with which interns (with clinician approval) actually delivered evidence-based preventive care advice to their patients when factors indicating such a need were present. 9,10 The audit postcurriculum change of Globe et al 9 showed virtually no difference in intern (and clinician) behaviors. Of 408 charts examined (204 before and 204 after the curriculum change), there were only 4 documented instances of appropriate recommendations for any of the 9 preventive health service categories, a startlingly low success rate of 1%.…”
Section: Upgrading the Clinical Preventive Services Curriculum-model mentioning
confidence: 98%
“…Chiropractors have always encouraged patients to take an active role in restoring and maintaining health, with particular emphasis on doctor-guided self-care through exercise and nutrition, 2 and new profession-wide initiatives reflect a deepened commitment to prevention and health promotion across the wide range of parameters elaborated by the U.S. Preventive Services Task Force. All students graduating from chiropractic colleges after January 2007 have been required to demonstrate knowledge of evidence-based prevention approaches and mastery of methods for applying these approaches in the clinical setting.…”
Section: Chiropractic: Time For Full Inclusionmentioning
confidence: 99%
“…Furthermore, surveys have documented that, in addition to their standard therapies (e.g., spinal manipulation), these providers are involved in a wide range of lifestyle counseling around issues such as physical activity and diet. 27,28 Although most CIH providers would readily recognize elements of public health in their regular patient care, in this report we focus on their potential role in community-wide public health efforts. Also, although we focus on chiropractic and naturopathic medicine, much of the information contained in this report is relevant to the other CIH professions, and perhaps to non-CIH health professions.…”
Section: The Overlap Between Public Health and Cihmentioning
confidence: 99%